Islamic science and the making of the European Renaissance - Saliba, George (Transformations (M.I.T. Press), 2007)
"The Islamic scientific tradition has been described many times in accounts of Islamic civilization and in general histories of science, with most authors tracing its beginnings to the appropriation of ideas from other ancient civilizations - the Greeks in particular. In this thought-provoking and original book, George Saliba argues that, contrary to the generally accepted view, the foundations of Islamic scientific thought were laid well before Greek sources were formally translated into Arabic in the ninth century. Drawing on an account by the tenth-century intellectual historian Ibn al-Nadim that is ignored by most modern scholars, Saliba suggests that early translations from mainly Persian and Greek sources outlining elementary scientific ideas for the use of government departments were the impetus for the development of the Islamic scientific tradition. He argues further that there was an organic relationship between the Islamic scientific thought that developed in later centuries and the science that came into being in Europe during the Renaissance."--Jacket